2016
DOI: 10.3847/0004-637x/821/2/83
|View full text |Cite
|
Sign up to set email alerts
|

Dark Post-Flare Loops Observed by the Solar Dynamics Observatory

Abstract: Solar post-flare loops (PFLs) are arcade-like loop systems that appear during the gradual phases of eruptive flares. The extreme ultraviolet (EUV) observations from the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory (SDO) allow us to investigate the fine structures in PFLs. In this work, we focus on studying the dark post-flare loops (DPFLs) during X-class flares, which are more evident in SDO/AIA data than in previous EUV data. We identify and analyze the DPFLs observed by SDO and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 111 publications
(166 reference statements)
2
9
0
Order By: Relevance
“…The sudden darkening of the bright EUV loop in our simulation resembles the dark postflare loop (DPFL) phenomenon, previously observed at the same 17.1 nm passband and with similar timescale of 10 minutes [32]. Observed DPFLs and the disappearing EUV coronal loop in our simulation also share the same time evolution of integral EUV flux: the EUV flux reaches its minimum value when the darkening happens (compare Fig.…”
Section: Coronal Rain and Dark Post-flare Loopssupporting
confidence: 85%
See 1 more Smart Citation
“…The sudden darkening of the bright EUV loop in our simulation resembles the dark postflare loop (DPFL) phenomenon, previously observed at the same 17.1 nm passband and with similar timescale of 10 minutes [32]. Observed DPFLs and the disappearing EUV coronal loop in our simulation also share the same time evolution of integral EUV flux: the EUV flux reaches its minimum value when the darkening happens (compare Fig.…”
Section: Coronal Rain and Dark Post-flare Loopssupporting
confidence: 85%
“…Another phenomenon thought to have a close relationship with these sudden condensations are the so-called dark post-flare loops (DPFLs), where some PFL loops suddenly vanish from specific EUV passbands, e.g. at 17.1 nm, 30.4 nm and 21.1 nm [32,33,34]. In these DPFLs, an EUV loop which was bright for a while suddenly darkens for several minutes, so effectively disappears between the adjacent EUV loops seen at the same height.…”
mentioning
confidence: 99%
“…These authors have highlighted multi-stranded and multi-thermal structure, but without reference to broad line widths. Plasma condensation after eruptive flares can produce similar phenomena (Song et al 2016), although the physical processes may differ. Kleint et al (2014) have found bursty flows associated with brightpoints at the edge of the sunspot umbra, that show a striking similarity to the profiles analyzed here, but lasting only ∼20 s.…”
Section: Introductionmentioning
confidence: 99%
“…The different observations in these different wavebands may indicate that this long line structure has a high temperature and it may be a current sheet produced by the magnetic reconnection of the eruption. The eruption was without significant X-ray enhancement, but had growing post-eruption arcades which are similar to the post-flare loops (Song et al 2016) and can be explained by the standard flare model. A CME can be observed from the image of SOHO/LASCO and it may cause disturbance to the interplanetary space.…”
Section: Resultsmentioning
confidence: 67%